Aislamiento microbiológico de superficies inanimadas en contacto con pacientes en un hospital peruano - Nahún R Plasencia-Dueñas (Asociación Colombiana de Infectología, 2021)
Objective: to describe the microbiological profile of inanimate surfaces in contact with the patient in a social security level III hospital in Chiclayo, Peru. Material and methods: An observational, descriptive, transversal study was carried out with the data from the reports of the Microbiological Qualitative Control of Physical Environments of 5 services of a Chiclayo Hospital level III in Peru. The method for the identification of microorganisms was the automated system VITEK MS. Descriptive analyses such as frequencies and percentages are presented. Results: A total of 177 isolations were reported, from which 97.74% (173) were positive, of these, 50.87% (88) were composed by gram-negative bacilli, being the most isolated microorganism Acinetobacter baumannii (17 samples) followed by Rhizobium radiobacter (16) and Sphingomonas paucimobilis13. Conclusions: The hospital environment is highly contaminated, being most of them pathogenic microorganisms. These results would be related to the long life of microorganisms on inert surfaces and the process of cleaning and disinfection of the hospital environment, so the evaluation of its effectiveness and the possible development of new and better cleaning techniques should be investigated.